Integrals revisited in 2019.

Calculus Level 4

Let n n be an odd integer greater than 1 1 . Suppose a unique function f : [ 0 , 1 ] R f : [0,1] \to \mathbb R satisfies

0 1 ( f ( x 1 k ) ) n k d x = k n \large\ \displaystyle \int _{ 0 }^{ 1 }{ { \left( f\left( { x }^{ \frac { 1 }{ k } } \right) \right) }^{ n - k }dx } = \frac { k }{ n }

for k = 1 , 2 , . . . , n 1. k = 1, 2, ..., n - 1.

Evaluate 2019 f ( 1 2019 ) 2019f\left( \large \frac { 1 }{ 2019 } \right) .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Priyanshu Mishra
Jun 20, 2019

Performing the substitution x 1 k = t { x }^{ \frac { 1 }{ k } } = t , the given conditions become

0 1 ( f ( t ) ) n k t k 1 d t = 1 n \large\ \displaystyle \int _{ 0 }^{ 1 }{ { \left( f\left( t \right) \right) }^{ n - k }{ t }^{ k - 1 }dt } = \frac { 1 }{ n } , k = 1 , 2 , . . . , n 1. k=1, 2, ..., n-1.

Observe that this equality also holds for k = n k = n . With this in mind we write

0 1 ( f ( t ) t ) n 1 d t = k = 1 n ( 1 ) k 1 ( n 1 k 1 ) 0 1 ( f ( t ) ) n k t k 1 d t = k = 1 n ( 1 ) k 1 ( n 1 k 1 ) 1 n = 1 n ( 1 1 ) n 1 = 0 \large\ \int _{ 0 }^{ 1 }{ { \left( f\left( t \right) -t \right) }^{ n-1 }dt } = \displaystyle \sum _{ k=1 }^{ n }{ \displaystyle { \left( -1 \right) }^{ k-1 }\begin{pmatrix} n-1 \\ k-1 \end{pmatrix} } \int _{ 0 }^{ 1 }{ { \left( f\left( t \right) \right) }^{ n-k }{ t }^{ k-1 }dt } = \displaystyle \sum _{ k=1 }^{ n }{ { \left( -1 \right) }^{ k-1 }\begin{pmatrix} n-1 \\ k-1 \end{pmatrix} } \frac { 1 }{ n } = \frac { 1 }{ n } { \left( 1-1 \right) }^{ n-1 } = 0

Because n 1 n-1 is even, ( f ( t ) t ) n 1 0 { \left( f\left( t \right) - t \right) }^{ n-1 } \ge 0 . The integral of this function can be zero only if f ( t ) t = 0 f (t) - t = 0 for all t [ 0 , 1 ] . t \in [0, 1]. Hence the only solution to the problem is f ( x ) = x . f(x) = x.

Great solution !.

Arghyadeep Chatterjee - 1 year, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...